Switching Lifestyles Is an in vivo Adaptive Strategy of Bacterial Pathogens - Desai, Stuti K.; Kenney, Linda J. (Frontiers in Cellular and Infection Microbiology, 2019)
Gram-positive and Gram-negative pathogens exist as planktonic cells only at limited times during their life cycle. In response to environmental signals such as temperature, pH, osmolality and nutrient availability, pathogenic bacteria can adopt varied cellular fates, which involves the activation of virulence gene programs and/or the induction of a sessile lifestyle to form multicellular surface-attached communities. In Salmonella, SsrB is the response regulator which governs the lifestyle switch from an intracellular virulent state to form dormant biofilms in chronically infected hosts. Using the Salmonella lifestyle switch as a paradigm, we herein compare how other pathogens alter their lifestyles to enable survival, colonization and persistence in response to different environmental cues. It is evident that lifestyle switching often involves transcriptional regulators and their modification as highlighted here. Phenotypic heterogeneity resulting from stochastic cellular processes can also drive lifestyle variation among members of a population, although this subject is not considered in the present review.